High-growth firm shares in Austrian regions: the role of economic structures. Issue 11 (1st November 2020) - Friesenbichler, Klaus; Hölzl, Werner
ABSTRACT: This paper explores the structural determinants of high-growth firm shares in Austrian regions. The regional level of analysis allows one to uncover regularities that are not detectable in firm-level studies. It is found that lower mobility barriers, firm exits and technological opportunities, measured by digitalization intensities, and, to a lesser extent, agglomeration effects are associated with a larger share of high-growth firms. The results suggest that comparisons of shares of high-growth firm across countries and regions should consider differences in the industrial structures together with the often-emphasized differences in policies and regulations.